Empyema Caused by Clostridium difficile - Darren A Hudson; A Patrick Gibb; M John Gill (Canadian Journal of Infectious Diseases)
Extraintestinal infections of Clostridium difficile are rare and often associated with underlying disorders. A case of empyema caused by aspiration of C difficile in a patient with carcinoid syndrome and C difficile colitis is described.